Climate change : a very short introduction - Maslin, Mark (Oxford : Oxford University Press, 2021)
In this edition of 'Climate Change', Mark Maslin explores all of the key debates. Examining the most recent scientific research, he looks what climate change is, its impact on our planet, and why it's such a complex problem to solve.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on August 9, 2021).
Keywords: Climatic changes; Global warming